The sea anemone Exaiptasia diaphana (Actiniaria, Aiptasiidae) associated to rhodoliths at Isla del Coco National Park, Costa Rica - Acuña, Fabian Horacio (2020)
Introduction: The sea anemones diversity is still poorly studied in Isla del Coco National Park, Costa Rica. Objective: To report for the first time the presence of the sea anemone Exaiptasia diaphana. Methods: Some rhodoliths were examined in situ in Punta Ulloa at 14 m depth, by SCUBA during the expedition UCRUNA-COCO-I to Isla del Coco National Park on 24th April 2010. Living anemones settled on rhodoliths were photographed and its external morphological features and measures were recorded in situ. Results: Several individuals of E. diaphana were observed on rodoliths and we repeatedly observed several small individuals of this sea anemone surrounding the largest individual in an area (presumably the founder sea anemone) on rhodoliths from Punta Ulloa. Conclusions: The geographic distribution is extended as well as their bathymetric distribution from the intertidal to 14 m depth. The photographs provide evidence of clonal reproduction by pedal laceration.